1990
DOI: 10.1002/food.19900340908
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between proteins, peptides and amino acids. New advances 1986–1989

Abstract: The paper deals with the recent achievements in the study of the various interactions between proteins, peptides and amino acids. The interactions are classified according to the hydrophilic, hydrophobic or mixed character of the interactive forces. The effect of the interaction on protein (peptide) association, structure and biological activity as well as the role of individual amino acid residues in the hydrophobic and hydrophilic interactions are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 87 publications
0
0
0
Order By: Relevance
“…Previous studies have reported that the hydrophobic effect plays a significant role in protein structure stabilization and folding in soymilk [16]. The apolar part of soy protein establishes intramolecular contacts and releases water, while hydrogen bonds in the protein backbone contribute to the association and stabilization of the protein structure [17]. Among all the papers, the 1:1-sized sample, with the highest concentration of soymilk, exhibits an excellent folding performance of soy protein on the surface.…”
Section: Analysis Of Sized Papermentioning
confidence: 99%
“…Previous studies have reported that the hydrophobic effect plays a significant role in protein structure stabilization and folding in soymilk [16]. The apolar part of soy protein establishes intramolecular contacts and releases water, while hydrogen bonds in the protein backbone contribute to the association and stabilization of the protein structure [17]. Among all the papers, the 1:1-sized sample, with the highest concentration of soymilk, exhibits an excellent folding performance of soy protein on the surface.…”
Section: Analysis Of Sized Papermentioning
confidence: 99%